Il trattamento delle condropatie degenerative con tessuto adiposo autologo microframmentato - Russo, A.; De Caro, F.; Condello, V.; Collarile, M.; Madonna, V. (Lo Scalpello - Journal, 2019)
TREATMENT OF DEGENERATIVE CARTILAGE LESIONS WITH MICRO-FRAGMENTED AUTOLOGOUS ADIPOSE TISSUE Osteoarthritis is a widespread pathology, with a prevalence of over 50% of the population, which leads to pain and functional limitation. At the moment, no surgical technique has been shown to be capable of real regeneration of the chondral layer. The new regenerative frontier seems to be represented by the self-ability of the Stromal Vascular Fraction (SVF) to preserve the cellular network, which is essential for cell regeneration. Several micro-fragmented adipose tissue extraction and processing systems have been refined in the past years and recent literature data show the biological effectiveness of this tissue, which plays a key role in restoring joint homeostasis, through the modulation of inflammation and pain. It will be necessary and important to understand whether this injective method can really be considered a “regenerative” option.